Arterial hypertension and natural remedies for its control. A suggestive proposal - Armiñana-García, Rafael (2024)
Hypertension has become one of the most prevalent conditions among Cuban adults and the main risk factor for morbidity and mortality due to cardiovascular causes. The action research was carried out in the Popular Council Van Troi in the town of Caibarién, province of Villa Clara, Cuba, and its objective was to propose different natural remedies for the control of arterial hypertension. For the development of the research, methods of information collection and processing of the information collected were used, such as observation, survey, interview, expert criteria, deductive-demonstrative, deductive-demonstrative, synthetic analytical, among others, and statistical and mathematical methods, where the descriptive statistic stood out, for the elaboration of the graphs and the percentage analysis was also used as a procedure. The sample consisted of 85 inhabitants of the town of Caibarién, showing deficiencies related to the use of home remedies for the control of Arterial Hypertension. In this sense, the written work on "Home remedies and Arterial Hypertension" was elaborated. The proposal was submitted to experts who evaluated it as very pertinent. These natural remedies are useful to complement the treatment for Arterial Hypertension.